Analisis Pengambilan Keputusan Pemerintah Kabupaten Sidoarjo untuk Melakukan Pembangunan Flyover Aloha - Nurwidya, Maharani Putri; Suci, Ken Maulida Musthika Tirta; Fitrie, Revienda Anita (As-Syirkah: Islamic Economic & Financial Journal, 2024)
In the midst of the hustle and bustle of activity and high mobility of society, Sidoarjo Regency, East Java, is faced with a crucial problem, namely traffic jams. Significant traffic congestion in the Sidoarjo area, which affects transportation efficiency and road user safety. This research uses qualitative research methods with literature studies, to investigate and analyze traffic congestion problems in the Sidoarjo area and to explore solutions that can be implemented to overcome these problems. The result is an evaluation of alternative policies to overcome traffic jams on Jalan Raya Aloha Sidoarjo. This research uses the Analytical Hierarchy Process (AHP) method to determine the most appropriate alternative policy to overcome this problem. The results of this research are about why the Aloha flyover is the most appropriate policy to overcome the problem of congestion on Jalan Raya Aloha. The decision to choose the flyover construction policy was because the policy met the criteria for overcoming congestion, namely reducing congestion, budget, quality and safety, ease of use and long-term benefits.